Standards and agricultural trade in Asia - Daniele Giovannucci; Timothy Purcell (Asian Development Bank Institute (ADBI), 2008)
In developing countries markets for agri-food products are changing at a pace that is unparalleled in modern history. Markets are increasingly open and increasingly homogenized toward international tastes and requirements for levels of quality, packaging, safety, and even process attributes such as socially or environmentally friendly methods. New distribution channels, dominated by larger firms including supermarket retailers, are imposing high performance demands on their value chains. In order to respond to these increasing market demands, developing countries are facing an inexorable shift toward more industrialized models of farming systems. This shift represents new challenges for small and medium farmers' access to markets and their ability to compete, as traditional standards are often no longer adequate even in some of the more lucrative national or internal markets. The key for many is to understand and achieve new levels of standards. The question for many countries-and not just developing countries-is what options are there for small farmers, which still comprise the great majority of the world's agricultural producers? Policy solutions will require a commitment to innovative institutional structures that can equitably link international capacity to local needs. A better understanding and collaboration with value chains via practical structures such as contract farming will help to ensure competitiveness and inclusion of small and medium-sized enterprises and smaller farmers.
Keywords: F12; Q12; D02; Q27; 330; Agraraußenhandel; Asien